Evidence for the Invalidity of the Wingate Test for the Assessment of Peak Power, Power Decrement and Muscular Fatigue - Jason Beam; Edson Estrada; Edson Estrada; Ann L. Gibson; Hung-Sheng Hsu; David Kennedy; Steve Lawson; Aditi Majumdar; Robert A Robergs; Roy M. Salgado; Gustavo Sierra; Ailish C. White; et al. (Wydawnictwo Naukowe Uniwersytetu Szczecińskiego, 2015)
We hypothesized that the protocol-induced initial cadence of the WAnT is too high to allow high muscle force production and peak power generation. Twenty endurance, strength or power trained subjects (9 male, 11 female) completed two 30 s maximal exertion stationary cycle ergometer tests involving the traditional peak cadence start (TRAD) vs. a stationary start (STAT). Inertia corrected mechanical power, cadence, EMG from the vastus lateralis, and applied force to the pedals were measured continuously throughout both tests. Peak power was higher during TRAD; 11.32 ±1.41 vs. 10.40 ±1.35 Watts/kg (p < 0.0001), as was peak cadence; 171.4 ±16.3 vs. 120.9 ±15.1 rev/min (p < 0.0001). However, during TRAD EMG root mean squared (rms) increased continuously throughout the test, force applied to the pedals increased from 1 to 3 s (0.73 ±0.27 vs. 0.90 ±0.39 N/kg; p = 0.02) and thereafter remained relatively stable. EMG mean frequency also increased from 1 to 3 s, but then decreased throughout the remainder of the test. During TRAD, mechanical power decreased near immediately despite increasing EMG rms, EMGmean frequency and force application to the pedals. The initial 10 s of data from the WAnT is invalid. We recommend that intense cycle ergometer testing should commence with a stationary start.